REVOLUTIONIZING HEALTHCARE DELIVERY: AN INSIGHT INTO WHOLE HEALTH APPROACH AND ROLE OF DATA SCIENCE - Mandhir , (JOURNAL OF COMPUTER ENGINEERING AND TECHNOLOGY (JCET), 2024)
This study provides insights into the transformative shift towards a holistic 'whole health' approach in healthcare delivery, focusing on the influence of social determinants of health on various health issues. It highlights how factors like poverty, lack of access to healthcare, and social isolation contribute to conditions such as malnutrition, mental health disorders, and chronic diseases. By understanding and addressing these social determinants, societies can mitigate health disparities and enhance overall public health outcomes. The abstract emphasizes the importance of public health interventions aimed at improving social and economic conditions to promote better health for all.